Psychoactive pharmaceuticals in aquatic systems: A comparative assessment of environmental monitoring approaches for water and fish - Grabicová, Kateřina; Grabic, Roman; Fedorova, Ganna; Kolářová, Jitka; Turek, Jan; Brooks, Bryan W; Randák, Tomáš (Environmental pollution (Barking, Essex, 2020)
Environmental monitoring and surveillance studies of pharmaceuticals routinely examine occurrence of substances without current information on human consumption patterns. We selected 10 streams with diverse annual flows and differentially influenced by population densities to examine surface water occurrence and fish accumulation of select psychoactive medicines, for which consumption is increasing in the Czech Republic. We then tested whether passive sampling can provide a useful surrogate for exposure to these substances through grab sampling, body burdens of young of year fish, and tissue specific accumulation of these psychoactive contaminants. We identified a statistically significant (p < 0.05) relationship between ambient grab samples and passive samplers in these streams when psychoactive contaminants were commonly quantitated by targeted liquid chromatography with tandem mass spectrometry, though we did not observe relationships between passive samplers and tissue specific pharmaceutical accumulation. We further observed smaller lotic systems with elevated contamination when municipal effluent discharges from more highly populated cities contributed a greater extent of instream flows. These findings identify the importance of understanding age and species specific differences in fish uptake, internal disposition, metabolism and elimination of psychoactive drugs across surface water quality gradients.
Keywords: Young-of-the-year fish; léčivé přípravky; Humans; Pharmaceutical Preparations; Environmental Monitoring; Water samples; lidé; zvířata; Fish tissues; chemické látky znečišťující vodu; POCIS; Cities; monitorování životního prostředí; voda; Czech Republic; Water Pollutants, Chemical; Water; Animals; Česká republika; velkoměsta; European chub